Penerapan Model Pembelajaran Kooperatif Berbasis Gamifikasi Dan Pengaruhnya Terhadap Hasil Belajar Matematika Pada Siswa SDN 1 Kayuambon Kelas 4 - Yasmin Hadiyya Fatin Hana; Az Zahra Salsabila; Muhammad Dzaky Al Ghifary; Muhammad Asykar Mu’thi (Universitas Maritim AMNI Semarang, 2024)
This reseacrh is intended to test the application of the gamification-based cooperative learning model and its influence on the mathematics learning outcomes of grade 4 students at SDN 1 Kayuambon. The cooperative model is a learning process that emphasizes cooperation and interaction so that students play an active role during the learning process. This cooperative learning model can be combined with a gamification-based learning model so that students can experience the learning process in a fun way. This research uses quantitative methods by comparing pretest and posttest data on the application of conventional models and gamification-based cooperative models. The research suggest an increase in learning outcomes in the pretest and posttest when the gamification-based cooperative model was applied by 8.14.